GIST case turned out to be a perforated peptic ulcer: a case report. Issue 10 (28th October 2021) - Miratashi Yazdi, Seyed Amir; Habibi, Pedram; Eftekhar Javadi, Arezoo; Hajebi, Reza
Abstract: Gastrointestinal stromal tumors (GISTs) are tumors arising from the fourth layer of the stomach. They are the most common form of mesenchymal neoplasms in the gastrointestinal tract. The diagnosis for the aforementioned tumors is made through endoscopic ultrasonography (EUS) with no further inspection through biopsies and aspirations. Regarding the fact that biopsies are not made in these cases, pathological misdiagnoses, however rare and effectless in the final outcome of the surgery, do occur. Here, we present a case of a 35-year-old male diagnosed with GIST through the means of EUS however, the post-op pathology report showed something very interesting. This patient was reported to be a case of perforated peptic ulcer and we found vegetable fiber component in the tissue of this patient. Bearing in mind the finding, misdiagnoses of GIST patients are probable, and careful planning prior to the surgery is recommended.